2011
DOI: 10.1038/icb.2010.171
|View full text |Cite
|
Sign up to set email alerts
|

CD27‐deficient mice show normal NK‐cell differentiation but impaired function upon stimulation

Abstract: Natural killer (NK) cells are part of the first line defense against tumors, parasites and virus-infected cells. Therefore, factors that control NK-cell numbers and their function are important. CD27 is constitutively expressed on NK cells and its expression correlates with sequential phases in NK-cell development, discriminating phenotypically and functionally different subsets within the NK-cell population. Although CD27 has been described to have an important regulatory role in effector and memory T and B l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…3C). Likely due to the low chance of separation of the CD27 gene and the Ly49 gene cluster, the Ly49H gene is missing in CD27 Ϫ/Ϫ mice backcrossed on a C57BL/6 background, which is consistent with a recent report that showed that CD27 Ϫ/Ϫ NK cells exhibit a 129/P2Ola-founded NK cell repertoire (36). To overcome this defect of Ly49H-dependent NK cell activation in CD27 Ϫ/Ϫ mice upon MCMV infection, an MCMV mutant lacking m157 (i.e., MCMV-⌬m157) was used.…”
Section: Cd27-cd70 Costimulation Promotes the Expansion Of Cmv-specifsupporting
confidence: 79%
“…3C). Likely due to the low chance of separation of the CD27 gene and the Ly49 gene cluster, the Ly49H gene is missing in CD27 Ϫ/Ϫ mice backcrossed on a C57BL/6 background, which is consistent with a recent report that showed that CD27 Ϫ/Ϫ NK cells exhibit a 129/P2Ola-founded NK cell repertoire (36). To overcome this defect of Ly49H-dependent NK cell activation in CD27 Ϫ/Ϫ mice upon MCMV infection, an MCMV mutant lacking m157 (i.e., MCMV-⌬m157) was used.…”
Section: Cd27-cd70 Costimulation Promotes the Expansion Of Cmv-specifsupporting
confidence: 79%
“…NK cells can promote tissue immune injury through NKG2D, an activating receptor on NK cells, during viral infection (3,32). In addition, CD27 is a costimulated molecule and can be upregulated on NK cells after viral infection, and CD27 ϩ NK cells have a stronger function with respect to cytokine secretion and cytotoxicity (7,13,29). Thus, we measured the expression of NKG2D and CD27 on NK cells within 72 h after RSV infection.…”
Section: Rsv Infection Induces Acute Lung Immune Injury In Micementioning
confidence: 99%
“…Other clinically relevant consequences of CD27 dysfunction might include: i) decreased memory formation to viral (including vaccine protein) antigens; 4,26 and ii) perturbed anti-tumor immunity of T cells, 27 gdT cells, 28 and NK cells, 29,30 potentially leading to an increased risk of other malignomas in addition to EBV-lymphomas. It is likely that more individuals with dysfunctional CD27 will be identified among patient cohorts with hypogammaglobulinemia (with or without EBV-LPD) and absent CD27-expressing memory B cells, potentially leading to the recognition of CD27 deficiency as a novel, albeit probably a rare, combined immunodeficiency.…”
Section: Immunological Consequencesmentioning
confidence: 99%